Clonal groups of Salmonella typhimurium in New York State. - McDonough, P L (1989)
The epidemiology of 278 strains of Salmonella typhimurium isolated from 1973 to 1981 from animals in New York State was studied by using four "fingerprinting" techniques, bacteriophage type (B.R. Callow, J. Hyg. 57:346-359, 1959), biotype (J. P. Duguid, E. S. Anderson, G. A. Alfredsson, R. Barker, and D. C. Old, J. Med. Microbiol. 8:149-166, 1975), plasmid profile, and antibiogram. Phage type with biotype was the most useful marker for distinguishing clonal groups of S. typhimurium. Four clones of S. typhimurium predominated, i.e., phage type/biotypes U275/26, 49/26, 10/3, and 2/3. U275/26 and 49/26 were commonly found until 1976, but clones 10/3 and 2/3 were predominant after 1976. Comparison of results with data from Canada suggested a dissemination of strains of S. typhimurium between Canada and New York. Cattle were a common source of phage type 49, as has been observed in other countries.